Avaliação experimental de um ciclone adaptado com bocais pulverizadores de água - Achiles, Ana Elisa (Universidade Federal de São Carlos, 2018)
Brazil is a world leader in the production of sugar and ethanol by using sugar cane. Nonetheless, in order to supply the energy demands of this sector, the sugarcane bagasse is used as a fuel in boilers and its burning generates a significant quantity of particulate matters which are highly nocive to the environment and human beings' health. Thus, this study objectives to evaluate, empirically, the performance of a cyclone adapted with liquid atomization nozzles for the purpose of collecting ashes that are derived from the burning of sugarcane bagasse and have median volumetric diameter of 7,47 μm. So, the behavior of collection efficiency and pressure drop was investigated through varying of the following parameters: gas inlet velocity (from 8,02 to 13,57 m/s); atomizer nozzle position; liquid-gas ratio (from 0,10 to 0,43 L/m³) and atomizer type (hollow and full cone). The overall collection efficiency was determinated by using the isokinetic sampling technique and the grade efficiency was obtained through the Aerodynamic Particle Sizer spectrometer. The results indicated that to atomize water into cyclones with a liquid-gas ratio of 0,43 L/m³ increased, significantly, the overall collection efficiency from 81,00 to 98,44%, and decreased the pressure drop from 657,1 to 392,3 Pa. With regarding to the grade efficiency, it was checked that water atomization increased, expressly, the fine particulate removal (PM_2,5) which are extremely harmful to human health. Furthemore, it was verified that the gas inlet velocity; the atomizer nozzle position; the liquid-gas ratio and the drop size distribution are parameters that affect the wet cyclone performance. Also, it was found out that the water spraying in cyclones declined, considerably, the outlet temperature of the gaseous stream in 20,2 °C, and raised its relative humidity in 42,5%. In general, it was achieved that water atomization in cyclones improves the performance of this equipment, especially the fine particles collection, apart from promoting the gas cooling and humidification. Hence, the wet cyclone showed to be a promising technology in removing particulate matter from gaseous stream.
Experimental evaluation of a cyclone adapted with water spray nozzles
Keywords: Ciclone; Lavadores de gás; Ciclone úmido; Atomização; Material particulado; Indústria sucroalcooleira; Eficiência de coleta; Limpeza de gás; Cyclone; Gas scrubber; Wet cyclone; Atomization; Particulate matter; Sugar and alcohol industry; Collection effiency; Gas treatment; ENGENHARIAS::ENGENHARIA QUIMICA::OPERACOES INDUSTRIAIS E EQUIPAMENTOS PARA ENGENHARIA QUIMICA; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA